Reproduction, cultural symbolism, and online relationship: Constructing city spatial imagery on TikTok - Liu, Nuochen; Sun, Xiaohui; Hong, Sha; Zhang, Bowen (Frontiers in Psychology, 2022)
The city on social media has become a hot topic in the study of city communication and city image. From the perspective of spatial theory and the communication characteristics of social media, this paper divides the spatial imagery of TikTok into three spaces: material space-cognitive attention, mental space-mental association, and relational space-emotional involvement. Based on the content analysis of 40 videos, we analyze the process of social media using cognition, association, and emotion as the starting points to increase the material space, expand the mental space, and expand the relational space. We find that spatial imagery can be co-constructed from the material space, mental space, and relational space. Lastly, the model is changed, and the value of using spatial theory to understand how city images are made is talked about.